BiblioTech : why libraries matter more than ever in the age of Google - Palfrey, John, 1972- (Basic Books, 2015)
"Libraries today are more important than ever. More than just book repositories, libraries can become bulwarks against some of the most crucial challenges of our age: unequal access to education, jobs, and information. In BiblioTech, educator and technology expert John Palfrey argues that anyone seeking to participate in the 21st century needs to understand how to find and use the vast stores of information available online. And libraries, which play a crucial role in making these skills and information available, are at risk. In order to survive our rapidly modernizing world and dwindling govergovernment funding, libraries must make the transition to a digital future as soon as possible by digitizing print material and ensuring that born-digital material is publicly available online."--Ebook Library